Improved detection and ambiguity resolution of low observable targets in MPRF radar - Hughes, Evan J.; Lewis, Michael B. (Cranfield University, 2009)
This paper presents the results of an investigation into the use of a Multiple Intelligent Software Agent technique as a means of eliminating ghost targets in a MPRF radar system especially when many real targets are present.